Evaluation of Ricinus communis L. for the Phytoremediation of Polluted Soil with Organochlorine Pesticides. (2nd August 2015) - Rissato, Sandra Regina; Galhiane, Mário Sergio; Fernandes, João Roberto; Gerenutti, Marli; Gomes, Homero Marques; Ribeiro, Renata; Almeida, Marcos Vinícius de
Abstract : Phytoremediation is an attractive alternative to conventional treatments of soil due to advantages such as low cost, large application areas, and the possibility of in situ treatment. This study presents the assessment of phytoremediation processes conducted under controlled experimental conditions to evaluate the ability of Ricinus communis L., tropical plant species, to promote the degradation of 15 persistent organic pollutants (POPs), in a 66-day period. The contaminants tested were hexachlorocyclohexane (HCH), DDT, heptachlor, aldrin, and others. Measurements made in rhizosphere soil indicate that the roots of the studied species reduce the concentration of pesticides. Results obtained during this study indicated that the higher the hydrophobicity of the organic compound and its molecular interaction with soil or root matrix the greater its tendency to concentrate in root tissues and the research showed the following trend: HCHs < diclofop-methyl < chlorpyrifos < methoxychlor < heptachlor epoxide < endrin < o, p′-DDE < heptachlor < dieldrin < aldrin < o, p′-DDT < p, p′-DDT by increasing order of log K o w values. The experimental results confirm the importance of vegetation in removing pollutants, obtaining remediation from 25% to 70%, and demonstrated that Ricinus communis L. can be used for the phytoremediation of such compounds.